Peternakan Udang Hias Air Tawar Neocaridinas dengan Metode Alami - Wulan, Dyah Ayu Tepus; Pratama, Aditya Willy; Firdaus, Muhammad Choliq; Saputra, Andon (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
As the development of the modern era, the beauty has a benefits for a healthy quality of life. The beauty is able to bring a sense of excitement, relaxation, and harmony in someones feelings. The phenomenon of public awareness about the importance of beauty is a big opportunity in the business, one of them is the ornamental aquarium containing shrimp which is a exclusive product of the room decoration to get profit, as well as a pioneer hobby, ornamental shrimp supplier for the hobbyists and stores. Through this ornamental shrimp farms, is expected to have a positive impact for traders shrimp or fish store that sells ornamental shrimp, is expected to reduce postage or transportation cost. Implementation through some process / method that structuring the location and design of the farm, where the second stage is the monitoring of water parameters and breed shrimp with natural methods because basically shrimp just need water parameters like their habitat to breed that is on the water with a ph range between 5 , 5-7.5, the third stage is the harvest. After the harvest is in the 4th month of the program, expected that shrimp are ready for sale. The Expectation outcomes are a product can be produced in the form of ornamental shrimp with good quality (brightly colored and bright as or better than the parent) and in the presence of ornamental shrimp farm business, the welfare of the members of the group can attempt to earn a profit, the future may be new jobs and can be ornamental shrimp supplier for resellers, shops, and hobbyists.Keywords : Farm, Ornamental Shrimp, Neocaridina sp